2020
DOI: 10.1002/pc.25590
|View full text |Cite
|
Sign up to set email alerts
|

The effect of filler localization on the properties of biopolymer blends, recent advances: A review

Abstract: In recent times, the field of biopolymer (BP) blends has been the focus of intensive fundamental and applied researches. Such BP combinations possess unique properties that are different from those of the individual components. However, most polyester polymers are thermodynamically immiscible because of their poor interactions. In the past, a third component, known as a well‐defined diblock or triblock copolymer, whose chemical structure is identical to that of the main components, was usually used as a compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 122 publications
0
15
0
Order By: Relevance
“…Further, the studies have indicated that nanoparticles with higher aspect ratios migrate faster than those with low ratios through a SlimFast mechanism. [109,[112][113][114][115] Therefore, it is imperative to realize the effect of filler localization in different blend phases as this will shed light on the structure-property relationship of the resulting composite system. Moreover, it is important to understand factors controlling the localization of filler in the specific blend matrices.…”
Section: Blend-based Compositesmentioning
confidence: 99%
“…Further, the studies have indicated that nanoparticles with higher aspect ratios migrate faster than those with low ratios through a SlimFast mechanism. [109,[112][113][114][115] Therefore, it is imperative to realize the effect of filler localization in different blend phases as this will shed light on the structure-property relationship of the resulting composite system. Moreover, it is important to understand factors controlling the localization of filler in the specific blend matrices.…”
Section: Blend-based Compositesmentioning
confidence: 99%
“…Polymeric nanocomposites based on metal oxide nanoparticles have attracted a lot of attention recently due to their excellent chemical, electrical, and optical characteristics. [1][2][3] As a result, they are now used in a variety of products, including sensors, solar cells, batteries, fuel cells, and supercapacitors. [4][5][6] By combining polymers with metal oxide nanoparticles in the composite's structure, it is possible to improve the electrical characteristics of certain polymers, such as conductivity and dielectric constant.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high strength-to-weight ratio, low cost, simplicity of availability, and ability to adjust the mechanical properties of polymer composites according to application needs, polymer composites have been widely used. Researchers [1][2][3][4][5][6] have been interested in using natural fibres and biopolymers as one of the constituent elements in composites for several decades, owing to environmental concerns and government laws. Synthetic polymers are combined with natural fibres and fillers to improve performance while reducing negative environmental impact.…”
Section: Introductionmentioning
confidence: 99%